Analysis of Furniture Industry Companies in Croatia - Andreja Pirc Barčić (University of Zagreb, Faculty of Forestry and Wood Technology, 2014)
Furniture manufacturing has always been a very important segment of the Croatian economy. In order to achieve better results of Croatian furniture industry potentials and to make appropriate and adequate changes, it is necessary to determinate the initial/current state of the company. The aim of this study was to analyze the general, production, technological, marketing and market segments in Croatian furniture industry companies. The study was conducted in Croatia in companies where furniture manufacturing is the main business activity. The analysis involved 77 out of 409 potential respondents. The analysis showed that the situation in Croatian furniture manufacturing companies is at a satisfactory level, although it is always necessary to seek, as much as it is possible, better company activates.